Determining the incidence of distraction among trauma patients in all modes of transportation. Issue 1 (July 2019) - Le, Brittany; Figueroa, Cesar; Anderson, Craig; Lotfipour, Shahram; Barrios, Cristobal
Abstract : BACKGROUND: The use of distracting technology is an increasing source of risk for injury among trauma patients. Both drivers and pedestrians show increased unsafe behavior. The data for prevalence and risk for distraction in trauma has varied widely. Our hypothesis is that distraction is more highly prevalent and widely distributed among all mechanisms of injury and variety of trauma patients. METHODS: A 10-question survey of adult trauma victims at a Level I trauma center regarding distraction at time of event was performed, examining age, sex, ethnicity, education level, mode of injury and role in the accident (driver, passenger, pedestrian, bicyclist, motorcyclist). Multiple-variable logistic regression was performed to identify risk factors for distraction. RESULTS: From June 2016 to October 2018, 1, 316 patients were surveyed, and 1, 011 (76.8%) patients reported their role in the traffic accident. The prevalence of distraction was 21.73% among drivers, 9.01% among passengers, 16.50% among pedestrians, 20.00% among bicyclists, and 8.09% among motorcyclists. Males (odds ratio [OR], 1.84; 95% confidence interval [CI], 1.26–2.67) as well as all Others (OR, 2.09; 95% CI, 1.10–3.98) showed statistically significant increased risk for distraction. Motorcyclist (OR, 0.25; 95% CI, 0.13–0.50) and passenger (OR, 0.37; 95% CI, 0.18–0.77) roles during collision were a lowered risk of distraction. Furthermore, Asian/Pacific Islanders (OR, 1.62; 95% CI, 0.94–2.79) trended toward being at greater risk for distraction. CONCLUSION: Distraction is prevalent among a wide range of traffic accident victims, not just drivers. Males as well as all Others are more likely to be distracted. In contrast, motorcyclists and passengers are less likely to be distracted. Further studies to assist in determining effective interventions and public safety efforts aimed at specific at-risk groups beyond motor vehicle drivers are warranted. LEVEL OF EVIDENCE: Epidemiological, level V.